When markets collide : investment strategies for the age of global economic change - El-Erian, Mohamed A., 1958- (New York : McGraw-Hill, 2008)
Written by the man who "Fortune" magazine refers to as a "Global Guru," "When Markets Collide" offers a cogent picture of the rapidly changing world financial system, and provides a detailed blueprint for capitalizing on the opportunities now available.
Aberrations, conundrums, and puzzles -- How traditional resources failed us -- Separating what matters from what doesn't -- Understanding the new destination -- Prospects for the journey -- Benefiting from global economic and financial change : an action plan for investors -- An action plan for national policy makers and global institutions -- Improved risk management -- Conclusion.
Includes bibliographical references (pages 313-325) and index.
BBS
Keywords: Markets; Business cycles; Risk management; Business & finance